Effects of Monetary Policy Announcements and Credibility on Inflation Expectations: Evidence for Colombia - Galvis Ciro, Juan Camilo; Anzoategui-Zapata, Juan Camilo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper refers to the literature on the effects of central bank announcements on inflation expectations in developing countries. In particular, based on the Colombian experience, we study the impact of interest rate announcements and macroeconomic shocks on breakeven inflation rates, given the monetary policy credibility scenario. The empirical evidence is implemented by regression analysis using an EGARCH model between 2008-2016. We find that inflation expectations respond to policy statements in Colombia. Our results show that the central bank pronouncements were more effective in anchoring expectations in the period 2012-2016 and the greater monetary policy credibility allows inflation expectations to be more stable before external shocks.